Agricultural intensification drives butterfly decline. Issue 4 (7th February 2019) - Habel, Jan Christian; Ulrich, Werner; Biburger, Nina; Seibold, Sebastian; Schmitt, Thomas
Abstract: Severe losses of insects have taken place over major parts of Europe. This negative trend is assumed to be largely the result of agricultural intensification. To analyse potential factors causing this loss of species, we assessed butterfly communities at 21 grassland patches. Seventeen of these were distributed across an agricultural landscape dominated by crop fields; four were embedded in two adjoining managed semi‐natural grassland areas. We assessed environmental parameters such as patch size and habitat quality for each grassland patch. We further incorporated the surrounding land‐cover considering different degrees of land‐use intensity. We classified butterfly species into generalists and specialists according their ecological and behavioural characteristics. As in the managed semi‐natural reference grasslands, species richness and abundance were higher in patches surrounded by extensively used grasslands and unsprayed crop fields, and lower in patches surrounded by sprayed crop fields. Furthermore, blossom density positively affected butterfly occurrence. Our data revealed that specialised butterfly species mainly occur in managed semi‐natural grassland sites, and are largely absent from other grassland plots embedded in the agricultural matrix. Our study underlines the negative impacts of intense conventional agriculture on butterfly species richness and abundance and reveals the urgent need for more nature‐friendly cultivation methods. In situ experiments may help to understand and disentangle single drivers causing this negative trend.